A robust combination of dysprosium vanadate/halloysite nanotubes: the electrochemical system for dimetridazole detection. (June 2022) - Kokulnathan, T.; Chen, T.-W.; Chen, S.-M.; Ahmed, F.; Hasan, P.M.Z.; Bilgrami, A.L.; Kumar, S.
Abstract: Dimetridazole (DMD) is one of the significant antibiotic drugs of nitroimidazoles derivates that have attracted increasing attention in the medical field due to its pharmacological and toxicological activity. The development of high-performance sensors for continuous monitoring of DMD in food and environments is receiving increasing attention. Herein, an electrochemical platform was designed based on a dysprosium vanadate/halloysite nanotubes (DyV/HNTs) nanocomposite for the detection of DMD. The DyV/HNTs nanocomposite was examined by various spectroscopic and analytical techniques. The DyV/HNTs based electrochemical sensor reveals a distinctly higher electrocatalytic response to the reduction of DMD due to the good physiochemical properties compared to other electrodes. The DyV/HNTs based electrochemical sensor for DMD covered two linear ranges of 0.001–0.54 and 0.54–188 μM with a detection limit of 0.9 nm through the amperometric method, which is better than those previously reported. Furthermore, selectivity, stability, repeatability, and reproducibility studies were performed. Moreover, the fabricated DyV/HNTs sensor was successfully applied for the reliable discrimination of DMD in biological and water samples with satisfactory recovery values. The results indicated that this DyV/HNTs nanocomposite may be a promising electrochemical sensing platform for the determination of DMD. Graphical abstract: Image 1 Highlights: The DyV/HNTs nanocomposite was prepared by hydrothermal method. The DyV/HNTs nanocomposite was fabricated for the determination of DMD. A very low detection limit of 0.9 nM DMD was achieved at the DyV/HNTs sensor. The DyV/HNTs sensor showed good DMD detection performance in real samples.